Hematologic parameters and bone marrow flow cytometry features in patients with GATA2 and RUNX1 germline mutations ; Evaluation of frequency of 11q aberrations in patients with Burkitt-like lymphoma and other aggressive B cell lymphomas: correlation with histopathology and clinical characteristics - HO, CHIA-CHEN (My University, 2022)
For patients presenting with cytopenias, the clinical presentation and histopathological distinction between an inherited (germline) bone marrow failure syndrome and an acquired bone marrow failure/myelodysplastic syndrome (MDS) can be challenging. Prompt and precise diagnosis of is critical to inform appropriate management before a leukemic transformation. GATA2 and RUNX1 are known germline pre-disposition mutations affecting master transcription factors important in lineage development. Here we aimed to develop a screening assay to help assess patients found to have germline GATA2 mutation and assist in germline variant curation. We compared the hematologic parameters and early bone marrow flow cytometric features in 8 patients with germline GATA2 mutations to 15 patients with aplastic anemia at our institution. To further consider the specificity of the findings in GATA2 deficiency patients, we compared their findings to 9 patients with germline RUNX1 mutations. Consistent with prior studies, our patients with GATA2 mutations showed less pronounced anemia and thrombocytopenia than those with aplastic anemia. Findings in the marrow, including the absence of hematogones, and reduction in NK cells, also support prior studies. Furthermore, compared to patients with RUNX1 mutations, patients with GATA2 mutations showed significantly lower B cells (of lymphocytes) and NK cells (of lymphocytes), and higher T cells (of lymphocytes). Interestingly, we also identified patients with RUNX1 mutations to have significantly more PDCs than patients with GATA2 mutations. Differences in our findings from prior studies, including similar peripheral blood absolute white counts, absolute neutrophils, absolute monocytes, absolute lymphocyte counts, and B cells or monocytes in the marrows of our patients with germline GATA2 mutations, are due to the small size of patient cohorts given the rarity of these germline variants as well as to variable disease status at presentation for evaluation/inclusion in these studies (i.e., pre-MDS, MDS). The combined findings contributed to the understanding of how these mutations establish variable pre-leukemic states predisposing to myeloid malignancies and supported the development of effective screening strategies. Burkitt-like lymphoma with 11q aberration (BLL-l1q) is one of the newly described provisional entities with morphologic features, immunophenotype, and gene expression profile similar to Burkitt lymphoma (BL) but lacks MYC rearrangement. Whether this entity is a distinct category or a variant of BL, diffuse large B cell lymphoma (DLBCL), or high-grade B cell lymphoma is still controversial. Few cases have been reported, leading to poor understanding of clinical presentations, treatment regimens, or full understanding of the landscape of mutations/copy-number alterations in BLL-11q. Here we aimed to evaluate the frequency of 11q aberration in our patients and their histopathologic characteristics, clinical presentations, and responses to therapy received. Thus, we performed genomic array on 10 BL patients in all ages, 5 DLBCL or HGBCL patients with CD10 or BCL6 positive and BCL2 negative under 60 years old (“Burkitt-like” group), and 4 DLBCL or HGBCL patients with CD10 or BCL6 positive and BCL2 positive under 60 years old. No typical 11q gain/loss pattern were found in our patients according to WHO classification at this time point. One patient in the BL group was identified with 11q terminal deletion, which is within the regions identified by prior BLL-11q studies. In addition to 11q aberrations, other findings in the BL group and the DLBCL or HGBCL with BCL2+ group further reflect previous studies on patients with BL and DLBCL. We concluded that the groups of patients are currently too limited for meaningful statistical assessment of the frequency of 11q aberrations, but suggest that 11q aberrations are not highly frequent in our “Burkitt-like” cases. We also observed the limitations on performing genomic array on older FFPE samples. Our future directions include requesting and running more recent samples, using stored RNA for transcriptome, and considering other significant findings in Burkitt-like patients without 11q aberrations.
Thesis (Master's)--University of Washington, 2021
Keywords: Burkitt-like lymphoma; GATA2; Germ-line; Hematologic maliganacies; RUNX1; Medicine; Laboratory medicine